Timeliness of Earnings Reported By Romanian Listed Companies - Mihai Carp; Constantin Toma (Journal of Accounting and Management Information Systems (JAMIS), 2018)
The paper aims to analyze the quality of financial information, by assessing the timeliness of earnings, using information specific to non-financial companies listed on the regulated section of Bucharest Stock Exchange. The study also seeks to assess the symmetry of actions for the timely recognition of potential gains and losses (components of the economic income) and, if there is an asymmetry, to identify the sense of the temporary gap. The phenomenon is analysed in conjunction with a number of control factors such as the Romanian Accounting Standards (RAS), the International Financial Reporting Standards (IFRS), the degree of indebtedness or the entities' field of activity. Quantitative analysis performed through econometric models consecrated in the field, such as Basu (1997) and Ball and Shivakumar (2005), reveals that the companies included in the study provide financial information that meets the qualitatively criterion assessed, respectively earnings timeliness. Deepening the analysis has made it possible to identify a timely recognition both for unrealised gains and potential losses, as a result of tests carried out on the whole sample, an advance in what concerns the inclusion of economic lose in the accounting income compared to the recognition of economic gains. The presence of disjunctive factors in the analysis generated a number of particular results. In the case of normally indebted companies that apply the IFRS, a timely recognition of economic gains and losses was noted, without the gap specific to conservatism.
Keywords: C13; C83; M41; M42; 650; financial information quality; timeliness of earnings; conservatism; IFRS; economic income